Determination of the optimal moment for the culling of breeding native guinea pigs (Cavia porcellus) - Quispe, Diana (2021)
In the Germplasm Bank of native guinea pigs of the EEA Chumbibamba of the National Institute of Agrarian Innovation (Peru) the optimal technical and economic moment for the single culling of breeding animals was determined. In total, 320 Creole guinea pigs were used and the Fisher-Hotelling methodology was applied, and the bioeconomic model of single harvest of breeding animals at constant price was proposed under four profitability rate scenarios. The results of the biological model indicate that the optimal productive life in females occurs at 414 days of age and in males at 579 days. The optimal values of the bioeconomic model for guinea pigs by profitability scenarios indicate that at a discount rate of 9%, the optimal harvest period would be 502 days; while at the discount rate of 30% it is reduced to 494 days.